Stereotactic irradiation of the resection cavity after surgical resection of brain metastases – when is the right timing?. (2nd December 2019) - Scharl, Sophia; Kirstein, Anna; Kessel, Kerstin A.; Diehl, Christian; Oechsner, Markus; Straube, Christoph; Meyer, Bernhard; Zimmer, Claus; Combs, Stephanie E.
Abstract: Purpose: This study aimed to evaluate whether an early beginning of the adjuvant stereotactic radiotherapy after macroscopic complete resection of 1–3 brain metastases is essential or whether longer intervals between surgery and radiotherapy are feasible. Material and methods : Sixty-six patients with 69 resection cavities treated with HFSRT after macroscopic complete resection of 1–3 brain metastases between 2009 and 2016 in our institution were included in this study. Overall survival, local recurrence and locoregional recurrence were evaluated depending on the time interval from surgery to the start of radiation therapy. Results: Patients that started radiotherapy within 21 days from surgery had a significantly decreased OS compared to patients treated after a longer interval from surgery ( p  < .01). There was no significant difference between patients treated ≥ 34 and 22–33 days from surgery ( p  = .210). In the univariate analysis, local control was superior for patients starting treatment 22–33 days from surgery compared to a later start ( p  = .049). This effect did not prevail in a multivariate model. There was no significant difference between patients treated within 21 days and patients treated more than 33 days after surgery ( p  = .203). Locoregional control was not influenced by RT timing ( p  = .508). Conclusion: A short delay in the start of radiotherapy does not seem to negatively impact the outcome in patients with resected brain metastases. We even observed an unexpected reduction in OS in patients treated within 21 days from surgery. Further studies are needed to define the optimal timing of postoperative radiotherapy to the resection cavity.